Empowerment of Mangrove Ecotourism - Annisa Solehatul J; Tutik Farihah; Noor Aliya Abdillah; Latifani Akyuni; Lutfi Sunani; Abdul Kadir Jailani; Rokhmad Joko Santoso; Karisma Dwi A; Sunarto Sunarto (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2018)
Kuliah Kerja Nyata (KKN or Student Community Service) is the program of UIN Sunan Kalijaga to devotion in society and providing change for the community. In this program we gave them knowledge about Local Potential of Mangrove Tourism in Jangkaran Village. This program is expected to make mangrove tourism as one of the famous touristThe aim of KKN Program are 1) Improve the management of mangrove tourism, 2) To complete the facilities and infrastructure of mangrove tourism, 3) Improve the awareness to mangrove tourism. The object of this study is the society and mangrove tourism in Jangkaran village. activity that have been done are clean up mangrove, procurement of trash bins, procurement of banner slogans, and planting mangroves. The result of the KKN program are maximizing mangrove forest potential as tourism and provide comfortable tourism facilities.